Вплив принципу мультисенсорності на забезпечення якості знань молодших школярів - Слабун, Олег (My University, 2025)
Магістерська робота складається з двох розділів. У першій частині, теоретичній, розкрито поняття «якість знань молодших школярів» у вимірах Нової української школи, надано педагогічну характеристику принципу мультисенсорності в освітньому процесі, та обґрунтовано відповідні педагогічні умови роботи. У другій частині, дослідницькій, розкрито суть та зміст проведення педагогічного експерименту, детально схарактеризовано практичні аспекти впровадження педагогічних умов впливу принципу мультисенсорності на забезпечення якості знань молодших школярів. Доведено ефективність цілеспрямованої реалізації даних умов. The work theoretically substantiates and experimentally verifies the impact of the multisensory principle on ensuring the quality of knowledge of primary school students. The essence and content of the multisensory principle in the educational process are revealed, multisensory learning technologies are characterized and their role in improving the quality of knowledge is determined. The indicators of knowledge quality are analyzed and their connection with the multisensory approach to learning is established. The psychophysiological foundations of sensory perception and classification of sensory channels of information perception are investigated. The role of visual, auditory and kinesthetic teaching methods in the formation of students’ knowledge, skills and abilities is determined. The possibilities of interactive learning tools and digital technologies in multisensory learning are analyzed.
Keywords: молодші школярі; якість знань; принцип мультисенсорності; педагогічні умови; multisensory principle; knowledge quality; primary school students; pedagogical conditions